Sonar Interface with FCS and Target Detection - V Asundi, Ravindra; L Narayanan, Anusha; B, Archana; H A, Ananya; Shrunga Divakara, C (International Journal of Engineering and Technology, 2018)
This paper presents a method to interface sound navigation and ranging(SONAR) with fire control system(FCS) and detection of targets. A submarine navigator keeps track of surrounding submarines and active targets such as torpedoes or mines and passive targets such as rocks, friend submarine or a ship, in order to have tactical information of its neighborhood. At present this is carried out manually by trained sonar operator. This task of classifying the object as either mines or rocks by training an artificial neural network using tensor flow framework, thereby giving the submarine (ship) system more autonomy. Â